Experiment and Simulation Investigation on the Tensile Behavior of Composite Laminate with Stitching Reinforcement. (15th November 2011) - Wang, Yi; Hou, Nai Xian; Yue, Zhu Feng
Abstract : The experiments and finite element simulations of composite laminate with stitching are carried out. Firstly, the monotonous tensile experiments with and without stitching are conducted to investigate the influence of stitch reinforcement on the composite laminate. Secondly, the finite element method (FEM) is employed to simulate the tensile process of specimens, and the link element is introduced to simulate the stitching. The experiment results shows that the stitching has little influence on the damage load under monotonous tensile load, while there is a significant influence on the changing of strain. The FEM results are consistent with the experiment results, which means that the link element can be used to study the stitching of the composite laminate. The simulation results also show that the distributions of strain are changed obviously due to the existence of the stitching. Research results have a significant role on the design of the composite structures with and without stitching.